STRUCTURES BIOLOGIQUES PRODUITES PAR LE SOUFRE DES VOLCANS ET FUMEROLLES - HERRERA, ALFONSO LUIS (ESCUELA NACIONAL PREPARATORIA, 1944)
A general description of methods and processes in cane sugar manufacture is given, with brief mention of beet sugar manufacture
BULL AMER MUS NAT HIST, NEW YORK
Keywords: STRUCTURES BIOLOGIQUES, SOUFRE, VOLCANS, FUMEROLLES; CIENCIAS DE LA VIDA; PALEONTOLOGIA; PALEONTOLOGIA ANIMAL